Significant photoelectrical response of epitaxial graphene grown on Si-terminated 6H-SiC - 郝昕 陈远富 王泽高 刘竞博 贺加瑞 李言荣 (Chinese physics B, 2013)
Photoelectrical response characteristics of epitaxial graphene （EG） films on Si- and C-terminated 6H-SiC, and transferred chemical vapor deposition （CVD） graphene films on Si-terminated 6H-SiC have been investigated. The results show that upon illumination by a xenon lamp, the photocurrent of EG grown on Si-terminated SiC significantly increases by 147.6%, while the photocurrents of EG grown on C-terminated SiC, and transferred CVD graphene on Si-terminated SiC slightly decrease by 0.5% and 2.7%, respectively. The interfacial buffer layer between EG and Si-terminated 6H-SiC is responsible for the significant photoelectrical response of EG. Its strong photoelectrical response makes it promising for optoelectronic applications.